Reforming translation education: The power of inquiry-based learning in translators’ cognitive development - Khalaf, Bilal; Al-Abbas, Linda; Mahmood, Ihab; Shabeeb, Taha; Mustafa, Sajjad (Edelweiss Applied Science and Technology, 2025)
Calls for reform in the field of translation have been sustained since the early days for being an independent field of knowledge. Recently, the importance of involving learners in educational settings has been highlighted as a meaningful strategy for improving cognition and academic expertise. This study designates Inquiry-Based Learning (IBL) as a learner-centered teaching paradigm in which students actively participate in cognitive activities. It aims to evaluate how IBL improves translators’ cognitive performance by encouraging better intellectual interaction with texts, situations, and the translation process. A qualitative design was utilized, which included classroom activities and journal entries from undergraduate translators who had been exposed to IBL-driven modules. The data were analyzed thematically to discover cognitive shifts and translators’ perspectives. The findings show that IBL improves cognitive awareness, promotes self-determination, and fosters responsive problem-solving abilities that are essential for successful translation. The study concludes that IBL creates a dynamic, reflective translator identity while strengthening cognitive ability. This study encourages educators to incorporate IBL into the translation curriculum to close the gap between classroom instruction and practical translation needs, thereby placing students as active knowledge producers. It also enables policymakers to assess and strengthen translators’ education.